Influence of hydrodynamic coupling on the electric linear dichroism of DNA fragments - Umazano, J.P. (2011)
In the present work, we study the effect of translational-rotational hydrodynamic coupling on the stationary electric linear dichroism of DNA fragments. The theoretical resolution of the problem has, so far, been dealt with analytic methods valid only in the limit of low electric fields. In this work, we apply numerical methods that allow us to study the problem and also consider electric fields of arbitrary strength. We use the bent rod molecules model to describe DNA fragments with physical properties characterized by their electric charge, electric polarizability tensor, rotational diffusion tensor, and translation-rotation coupling diffusion tensor. The necessary orientational distribution function to calculate electric dichroism is obtained by solving the Fokker-Planck equation through the finite difference method. We analyze the different contributions due to electric polarizability and translational- rotational coupling to the electric dichroism. © 2011 American Institute of Physics.